Optimasi Penggunaan Karagenan dan Kalsium Sulfat pada Pembuatan Tahu Sutra dalam Penembangan Pangan Fungsional: Optimization the Use of Carrageenan and Calcium Sulfate in Silken Tofu Production in Functional Food Development - Palupi, Nurheni Sri; Indrastuti, Nindya Atika; Uju; Syamsir, Elvira (Jurnal Pengolahan Hasil Perikanan Indonesia, 2020)
Silken tofu dessert is traditional food consist of silken tofu and ginger soup. Soybean and ginger which are the main raw ingredients of the traditional food have been known for its functional properties when consumed. This makes wedang tahu potentially developed as a functional food. The texture quality of silken tofu is the main factor that determines the quality of wedang tahu. The addition of carrageenan in the wedang tahu processing is expected to improve the quality of silken tofu produced. This study was aimed to determine the combination of calcium sulfate concentration and carrageenan in order to optimize the yields and texture of silken tofu produced by using the Design Expert software version 7.0. The determination of optimum formula was based on visual observation (subjective) which was correlated with the results of texture measurement objectively by using the TA-XT2i Texture Analyzer. The optimum formula was then followed by a sensory test, proximate test, recommended dietary allowance (RDI), texture test, as well as syneresis test. The optimum formula recommended was a combination of 0.45% calcium sulfate and 0.10% carrageenan with a desirability value of 0.75. The yield, hardness, cohesiveness, elasticity and chewing value of its formula were 85.36%, 173.60 gf, 0.07, 0.54, and 6.58 gf respectively.